2003
DOI: 10.1554/02-768
|View full text |Cite
|
Sign up to set email alerts
|

Life-History Differentiation and the Maintenance of Monoecy and Dioecy in Sagittaria Latifolia (Alismataceae)

Abstract: The existence of monoecious and dioecious populations within plant species is rare. This limits opportunities to investigate the ecological mechanisms responsible for the evolution and maintenance of these contrasting sexual systems. In Sagittaria latifolia, an aquatic flowering plant, monoecious and dioecious populations exist in close geographic proximity but occupy distinct wetland habitats differing in the relative importance of disturbance and competition, respectively. Life-history theory predicts contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…However, this prediction was rejected in S. latifolia because genetic estimates of clone size indicated the opposite pattern, with larger clones in monoecious than dioecious populations (46). Monoecious populations are adapted to temporary aquatic habitats (e.g., ditches, farm ponds), which probably explains why they have higher vegetative growth rates and corm production than dioecious populations, which are more commonly found in permanent wetlands (48). This difference in life history may explain the observed difference in clone size between the sexual systems.…”
Section: Clonality In Plants With Sexual Polymorphismsmentioning
confidence: 99%
“…However, this prediction was rejected in S. latifolia because genetic estimates of clone size indicated the opposite pattern, with larger clones in monoecious than dioecious populations (46). Monoecious populations are adapted to temporary aquatic habitats (e.g., ditches, farm ponds), which probably explains why they have higher vegetative growth rates and corm production than dioecious populations, which are more commonly found in permanent wetlands (48). This difference in life history may explain the observed difference in clone size between the sexual systems.…”
Section: Clonality In Plants With Sexual Polymorphismsmentioning
confidence: 99%
“…Monoecious populations commonly occupy ephemeral aquatic habitats such as ditches and farm ponds, whereas dioecious populations are found in more stable wetland habitats associated with large lakes and extensive river systems (Dorken et al 2002). Common garden and transplant studies have demonstrated that populations of the two sexual systems are differentiated from one another, possessing a suite of life-history traits associated with adaptation to their contrasting wetland habitats (Dorken & Barrett 2003). Crossing studies indicate no barriers to inter-fertility between the sexual systems and patterns of genetic differentiation at neutral loci suggest that ecological differentiation limits extensive gene flow between the sexual systems (Dorken et al 2002).…”
Section: Evolution Of Dioecy and Related Gender Strategiesmentioning
confidence: 99%
“…Analysing variation in reproductive strategies in hybridizing taxa provides an excellent opportunity for directly studying the factors that influence the evolutionary pathway between different reproductive systems (Barrett, 1998;Charlesworth, 1999;Hewitt, 2001;Dorken et al, 2002;Dorken & Barrett, 2003). While changes in the mating system can influence the degree of reproductive isolation of the parental species, reproductive isolation may also evolve due to divergent selective pressures in different habitats (e.g.…”
Section: Introductionmentioning
confidence: 99%